Changes in precarious employment in the United States: A longitudinal analysis - Oddo, Vanessa M.; Zhuang, Castiel Chen; Andrea, Sarah B.; Eisenberg-Guyot, Jerzy; Peckham, Trevor; Jacoby, Daniel; Hajat, Anjum (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVE ': 'This longitudinal study aimed to measure precarious employment in the US using a multidimensional indicator. ' ' METHODS ': 'We used data from the National Longitudinal Survey of Youth (1988–2016) and the Occupational Information Network database to create a longitudinal precarious employment score (PES) among 7568 employed individuals over 18 waves (N=101 290 observations). We identified 13 survey indicators to operationalize 7 dimensions of precarious employment, which we included in our PES (range: 0–7, with 7 indicating the most precarious): material rewards, working-time arrangements, stability, workers’ rights, collective organization, interpersonal relations, and training. Using generalized estimating equations, we estimated the mean PES and changes over time in the PES overall and by race/ethnicity, gender, education, income, and region. ' ' RESULTS ': 'On average, the PES was 3.17 [standard deviation (SD) 1.19], and was higher among women (3.34, SD 1.20), people of color (Hispanics: 3.24, SD 1.23; non-Hispanic Blacks: 3.31, SD 1.23), those with less education (primary: 3.99, SD 1.07; high school: 3.43, SD 1.19), and with lower-incomes (3.84, SD 1.08), and those residing in the South (3.23, SD 1.17). From 1988 to 2016, the PES increased by 9% on average [0.29 points; 95% confidence interval (CI) 0.26–0.31]. While precarious employment increased over time across all subgroups, the increase was largest among males (0.35 points; 95% CI 0.33–0.39), higher-income (0.39 points; 95% CI 0.36–0.42) and college-educated (0.37 points; 95% CI 0.33–0.41) individuals. ' ' CONCLUSIONS ': 'Long-term decreases in employment quality are widespread in the US. Women and those from racialized and less-educated populations remain disproportionately precariously employed; however, we observed the largest increases among men, college graduates and higher-income individuals.
Keywords: employment condition; employment quality; health disparity; longitudinal; non-standard work; precarious employment; precarious work; precarity; United States